Crystallographic and DFT Studies on Pyrrolo[1, 2-c]imidazole Scaffolds. (14th April 2014) - Jayaraman, Manikandan; Balakrishnan, Rajarathinam; Muthu, Kannan; Panneerselvam, Manivel; Gnanasambandam, Vasuki; Ramadas, Krishna
Abstract : The crystal structures of the compounds C15 H14 N4 O2 (1 ) and C16 H16 N4 O4 (2 ) are reported and analyzed by single crystal X-ray diffraction technique. Compounds (1 ) and (2 ) crystallized in monoclinic space group P21/c and Cc with four molecules in the unit cell, respectively. The unit cell parameters for compound (1 ) area = 11.4501(15) Å, b = 9.7869(11) Å, c = 12.3653(15) Å, β = 90.997(11)°, and Volume = 1385.5(3) Å 3 and for compound (2 ) area = 13.865(2) Å, b = 6.9538(8) Å, c = 16.841(2) Å, β = 98.602(11)°, and Volume = 1605.4(4) Å 3 . In both compounds (1 ) and (2 ), the pyrrolidine ring adopts half-chair conformation. Moreover, both inter- and intramolecular N–H ⋯ O hydrogen bonds stabilize the crystal structure and play a crucial role in crystal packing. This intermolecular interaction alone constructsC 1 1 chain motif in both compounds. It is also supported by weak intermolecular π - π interaction which is essential for the stability of the crystal packing. Further, the Density Functional Theory (B3LYP) method with standard 6-31G basis set was used in the calculation and calculated geometrical parameter is correlated with the corresponding experimental data. The obtained HOMO and LUMO energies are in negative values indicating that the compounds are in stable state.